KN - Journal of Cartography and Geographic Information Kartographische Nachrichten - Vetter, Mark.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
KN - Journal of Cartography and Geographic Information is dedicated to theoretical, applied and empirical approaches of cartography and geovisualization. We understand cartography as a science and technique to analyze, visualize and communicate spatial information. Cartography is the cross-over discipline in the field of spatial and geo sciences, including geoinformation science. Cartography addresses spatial questions from a variety of disciplines, including geography, environmental sciences and social sciences, using methods and tools developed at the interface with neighboring domains such as geodesy, GI Science, and spatial cognition. These questions can put different emphasis on theoretical fundamentals, methods, techniques and applications. KN - Journal of Cartography and Geographic Information is the only cartographic journal of the German language area. The journal is among the oldest cartographic periodicals worldwide. It was established in 1951 as the journal of the German Society of Cartography (DGfK). In 1976, the journal has become the joint periodical publication of DGfK, the Cartographic Commission of the Austrian Geographical Society (ÖKK), and the Swiss Cartographic Society (SGK). The journal publishes four issues per year. All articles are peer-reviewed. Furthermore, there are short articles on recent technical developments in practical applications with geodata. The journal reports on national as well as international conferences and other events concerning the above-mentioned fields. Supplementary sections comprise regular accounts of the activities in the German, Austrian and Swiss cartographic societies and business news from private-sector-companies, government agencies and academia. In addition, there are book reviews and a calendar of cartographically relevant events. Since 2009, the journal is indexed in Scopus.
Keywords: Natural disasters; Geography; Geographical information systems; Mathematics; Visualization; Human geography; Geographical Information Systems/Cartography.; Geography, general; Human Geography; Natural Hazards; Web Development; Visualization